Stateless : the politics of the Armenian language in exile - Chahinian, Talar (Syracuse University Press, 2023)
"In this important study, the author examines Western Armenian language and literature following the 1915 genocide and the flight of survivors to various locations around the world. Chahinian highlights two specific time periods and cities-post-WWI Paris and post-WWII Beirut-to explore how Western Armenian literature evolved in the diaspora"--